2023
DOI: 10.1002/fsn3.3310
|View full text |Cite
|
Sign up to set email alerts
|

Individual nutrients and serum klotho levels in adults aged 40–79 years

Abstract: Several dietary factors (including adherence to the Mediterranean diet or higher nut intake) seem to positively affect circulating antiaging Klotho protein levels; yet, a description of possible relationships between individual nutrients and Klotho activity has not been evaluated. We analyzed the association of dietary intake of individual macro‐ and micronutrients and nonnutritive food components with circulating Klotho levels in a sample of 40‐ to 79‐year‐old US adults. Data from the 2015–2016 National Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…However, in the FIT-AGEING study (n = 72) [ 21 ], De-la-O et al found a negative correlation between carbohydrate intake and serum Klotho levels in females, but this correlation disappeared after controlling for covariates such as age, lean body mass index, and sedentary time. In contrast, Ostojic et al [ 19 ] reported a positive association between higher carbohydrate intake and soluble Klotho levels after adjusting for age and gender (n = 2637). Overall, these studies suggest that no consensus has been reached on the relationship between carbohydrate intake and Klotho levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in the FIT-AGEING study (n = 72) [ 21 ], De-la-O et al found a negative correlation between carbohydrate intake and serum Klotho levels in females, but this correlation disappeared after controlling for covariates such as age, lean body mass index, and sedentary time. In contrast, Ostojic et al [ 19 ] reported a positive association between higher carbohydrate intake and soluble Klotho levels after adjusting for age and gender (n = 2637). Overall, these studies suggest that no consensus has been reached on the relationship between carbohydrate intake and Klotho levels.…”
Section: Discussionmentioning
confidence: 91%
“…However, a comprehensive link between carbohydrate intake levels and serum Klotho remains relatively unexplored in the existing literature. While an epidemiological study has suggested a synchronous increase between carbohydrate intake and soluble Klotho levels in the population [ 19 ], experimental research has further supported this finding [ 20 ]. Some experimental studies have indicated that a high-sucrose diet can elevate Klotho levels in mice compared to control mice.…”
Section: Introductionmentioning
confidence: 99%
“…The National Health and Nutrition Examination Survey (NHANES) is a serial cross‐sectional survey that collects data on the nutritional and health status of the noninstitutionalized US population (Ostojic et al., 2023 ; Sun et al., 2023 ). This nationwide survey provides data through questionnaires, physical examinations, and laboratory tests (Ahluwalia et al., 2016 ; Shen et al., 2023 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, Klotho level happens to be influenced by the inflammatory and oxidative stress status of the body [ 28 , 35 ]. It has been reported that there is an association between dietary fiber intake and serum Klotho levels [ 36 ]. However, in-depth epidemiological studies of the relationship between these two based on large population samples are sorely lacking, and they deserve further exploration.…”
Section: Introductionmentioning
confidence: 99%